2011
DOI: 10.1002/ijc.26368
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor protein kinase Chk2 is a mediator of anoikis of intestinal epithelial cells

Abstract: Resistance of carcinoma cells to anoikis, apoptosis that is normally induced by detachment of nonmalignant epithelial cells from the extracellular matrix, is thought to be critical for carcinoma progression. Molecular mechanisms that control anoikis of nonmalignant and cancer cells are understood poorly. In an effort to understand them we found that detachment of nonmalignant intestinal epithelial cells triggers upregulation of Chk2, a pro-apoptotic protein kinase that has never been implicated in anoikis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Anoikis resistance is one of the acquired capabilities of tumorigenic cells to disseminate. Increased oncogene and decreased tumor suppressor genes expression can improve protection from anoikis [61], [62]. In this study, melan-a melanocyte lineage submitted to anchorage blockade presented Ras activation in the first 30 minutes ( Figure 2A ) and some authors have demonstrated that Ras signaling can affect gene expression through DNA methylation.…”
Section: Discussionmentioning
confidence: 52%
“…Anoikis resistance is one of the acquired capabilities of tumorigenic cells to disseminate. Increased oncogene and decreased tumor suppressor genes expression can improve protection from anoikis [61], [62]. In this study, melan-a melanocyte lineage submitted to anchorage blockade presented Ras activation in the first 30 minutes ( Figure 2A ) and some authors have demonstrated that Ras signaling can affect gene expression through DNA methylation.…”
Section: Discussionmentioning
confidence: 52%
“…Our study, for the first time, identified CHK2 as a novel mediator of anoikis in PTC cells, as has already been reported in intestinal epithelial cells [48]. Anoikis resistance is a hallmark of malignant cells and is believed to play a role in the survival of circulating tumor cells.…”
Section: Discussionmentioning
confidence: 49%
“…We found previously that anoikis of intestinal epithelial cells is driven by multiple mechanisms mediated by detachment-induced changes in the expression of various regulators of apoptosis. 4,18,24,25 Importantly for this study, we and others observed previously that a small fraction of nonmalignant intestinal epithelial cells, such as IEC-18 and Hkh-2 used in this study, remains viable after being cultured without adhesion to the ECM and if expanded displays pronounced and well reproducible resistance to anoikis 22,23 (the nature of this cellular heterogeneity is presently not known). These data indicate that intestinal epithelial cells contain a cell population in which at least some of the anoikis-promoting mechanisms are blocked.…”
Section: Discussionmentioning
confidence: 70%
“…4,24,25 We also established that oncogenic RAS, an oncoprotein that often occurs in colorectal cancer, blocks anoikis of colon cancer cells via multiple mechanisms that involve the downregulation of pro-apoptotic proteins BAK1/Bak and CASP2/caspase-2 and the upregulation of BCL2L1 as well as that of apoptosis inhibitors BIRC3/cIAP2 and XIAP. 4,5,18,26 In searching for the mechanisms by which detachment of nonmalignant intestinal epithelial cells blocks their growth we found that growth arrest of detached cells is driven by their detachment-induced autophagy.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation